Social networks in the boardroom - Francis Kramarz; David Thesmar (Institute for the Study of Labor (IZA), 2006)
This paper provides empirical evidence consistent with the facts that (1) social networks may strongly affect board composition and (2) social networks may be detrimental to corporate governance. Our empirical investigation relies on a unique dataset on executives and outside directors of corporations listed on the Paris stock exchange over the 1992-2003 period. This data source is a matched employer employee dataset providing both detailed information on directors/CEOs and information on the firm employing them. We first find a very strong and robust correlation between the CEO's network and that of his directors. Networks of former high ranking civil servants are the most active in shaping board composition. Our identification strategy takes into account (1) differences in unobserved directors' abilities and (2) the unobserved propensity of firms to hire directors from particular networks, irrespective of the CEO's identity. We then show that the governance of firms run by former civil servants is relatively worse on many dimensions. Former civil servants are less likely to leave their CEO job when their firm performs badly. Secondly, CEOs who are former bureaucrats are more likely to accumulate directorships, and the more they do, the less profitable is the firm they run. Thirdly, the value created by acquisitions made by former bureaucrats is lower. All in all, these firms are less profitable on average.
Keywords: J40; L20; Z13; 330; networks; corporate governance; Corporate Governance; Führungskräfte; Vorstand; Betriebsergebnis; Kapitalgesellschaft; Schätzung; Frankreich